The bromeliad leaf-scraper tortoise beetle Spaethiella intricata (Boheman, 1850) from Brazil (Coleoptera, Chrysomelidae, Cassidinae), description of immatures and biology - Albertoni, Fabiano F.; Leocádio, Michele (Zootaxa, 2018)
This publication describes the life history and morphology of the immatures of Spaethiella intricata associated with bromeliads. Immature stages were previously unknown for the species. Adults and larvae are bromeliad leaf scrapers. First and fifth instar larvae and pupa of S. intricata are described and illustrated with further discussion upon the epipharynx of some Cassidinae species belonging to few tribes. General observations of the known Hemisphaerotini immatures and adults are compared.